Growth, Water Use, and Nitrate-15N Uptake of Greenhouse Tomato as Influenced by Different Irrigation Patterns, 15N Labeled Depths, and Transplant Times - Hou, Maomao; Jin, Qiu; Lu, Xinyu; Li, Jiyu; Zhong, Huizhen; Gao, Yue (Frontiers in Plant Science, 2017)
Increasing water use efficiency and reducing nitrogen pollutant discharge are important tasks for modern agriculture. To evaluate the effect of alternate partial root-zone irrigation (APRI) on tomato plant growth, water use efficiency and nitrate-15N uptake, an experiment was conducted from June to December in 2014 under greenhouse condition in northern China. The experiment contained two irrigation patterns [APRI and conventional irrigation (CI)], two 15N labeled depths in soil (10 and 50 cm) and two transplant time (early and late summer). Results showed that, compared to CI, APRI did not significantly (p > 0.05) impact the growth and biomass accumulation in aboveground part of tomato, while it enhanced the root, reflecting by greater length density, and more dry mass. APRI produced marginally lower yields, but saved 34.9% of irrigation water, and gave a 37.6–49.9% higher water use efficiency relative to CI. In addition, APRI improved fruit quality, mainly through increasing the contents of soluble solid (by 12.8–21.6%), and vitamin C (2.8–12.7%), and the sugar/acid ratio (3.5–8.5%). The 15N utilization efficiency (15NUE) in APRI was higher than that in CI, which was more evident when 15N was labeled at 50 cm depth. Significant (p < 0.05) 15N recovery increase of 10.2–13.2% and 15N loss decrease of 35.4–54.6% were found for APRI compared to CI. The overall results suggest that APRI under greenhouse could benefit the nitrate-N recovery and increase the water use efficiency in tomato.